2012
DOI: 10.5897/ajb09.1337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rhizobia and plant growth promoting bacteria inoculation on germination and seedling vigor of lowland rice

Abstract: Plant growth promoting rhizobacteria (PGPR) stimulate plant growth by producing phytohormone which enhances the growth and physiological activities of the host plant. Recently, legume bacteria (Rhizobium spp.) have been considered as a PGPR for legume as well as non-legumes and have the potential for growth stimulation. A laboratory experiment was conducted to observe the effect of PGPR and Rhizobial inoculation on seed germination, seedling emergence, growth and development of lowland rice variety MR219. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…The treatment with isolate M4 also sped up germination, when compared with the negative control (Table 2), but it did not alter the germination rate. Likewise, Mia et al (2012) found a higher growth of rice (Oryza sativa L.) in the presence of Bacillus sphaericus; however, as in the present study, the germination rate did not vary.…”
Section: Resultscontrasting
confidence: 46%
“…The treatment with isolate M4 also sped up germination, when compared with the negative control (Table 2), but it did not alter the germination rate. Likewise, Mia et al (2012) found a higher growth of rice (Oryza sativa L.) in the presence of Bacillus sphaericus; however, as in the present study, the germination rate did not vary.…”
Section: Resultscontrasting
confidence: 46%
“…In their case, inoculation with bacterial isolates which produced IAA caused longer primary roots of canola and more numerous adventitious roots in mung bean cuttings. PGPR and rhizobia have been suggested to stimulate growth of rice seedlings by producing phytohormones, particularly IAA, which promote seed emergence and other seedling attributes (Mia et al, 2012;Keyeo et al, 2011). Battacharjee et al (2012) also found that rhizobial strain namely Rhizobium leguminosarum could secrete phytohormones such as IAA and increase the biomass, root branching and N content of rice plants.…”
Section: Ajabsmentioning
confidence: 99%
“…Research on Plant Growth-Promoting Rhizobacteria (PGPR) with non-legumes such as rice have shown beneficial effects through biological N 2 fixation (Malik et al, 1997), increased root growth (Mia et al, 2012) with enhanced nutrient uptake (Yanni et al, 1997), phytohormone production (Chabot et al, 1996), plant growth enhancement stimulation by other beneficial bacteria and fungi (Saharan and Nehra, 2011) and disease control (Ramamoorthy et al, 2001). Peng et al (2002), however, reported that rhizobial inoculation known for their symbiotic relationship with legumes, could also increaserice grain yield, but little is known about the mechanism(s) involved.…”
Section: Introductionmentioning
confidence: 99%
“…Endophytic bacteria are microorganisms living inside plants without creating noxious efficacy [9]. Many endophytic bacteria that are in strong contact with seeds may have adapted to link with embryos or seedlings to regulate seedling growth [10][11][12][13][14] and improve plant growth through enhanced nutrient uptake, nitrogen fixation, synthesis of enzymes, siderophores production and growth phytohormones [15][16][17][18][19]. Bio-priming organisms with PGPB comprise species of the genera Pseudomonas and Bacillus [20,21] along with Burkholderia, Stenotrophomonas, Micrococcus, Rhizobium, and Pantoea, Microbacterium [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%